2023
DOI: 10.1097/cji.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment CD8 T and Treg Cells–related Genes Signature Distinguishes Distinct Prognosis and Targeted Therapies Response in Endometrial Cancer

Abstract: Although most endometrial cancer (EC) patients have a favorable prognosis, the overall survival (OS) of metastatic and recurrent EC could hardly be improved by the current chemoradiotherapy. We aimed to reveal the tumor microenvironment immune infiltration characteristics to elucidate the underlying mechanism of EC progression and guide clinical decisions. In the Cancer Genome Atlas (TCGA) cohort, Kaplan-Meier survival curves confirmed Tregs and CD8 T cells were prognosis-protective factors in OS of EC (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…First, with immune checkpoint therapy showing varying response rates, the pursuit of precision therapy becomes crucial for maximizing clinical benefits. 29 , 30 , 72 Under the circumstances, numerous studies have searched for prediction markers for immunotherapy response from the perspective of immune cells, molecules, and tumor mutation 73 , 74 , 75 , 76 , 77 More and more evidence has pointed out that tumor metabolism reprogramming has wider implications in the regulation of antitumor immune response influencing immune cell differentiation and function. 1 , 78 , 79 In our study, the MPS2 subgroup had abundant infiltration of immune cells with antitumor function and higher expression of immune molecules, whereas immune dysregulation within the TME prevented the immune cells from exerting their full effects in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…First, with immune checkpoint therapy showing varying response rates, the pursuit of precision therapy becomes crucial for maximizing clinical benefits. 29 , 30 , 72 Under the circumstances, numerous studies have searched for prediction markers for immunotherapy response from the perspective of immune cells, molecules, and tumor mutation 73 , 74 , 75 , 76 , 77 More and more evidence has pointed out that tumor metabolism reprogramming has wider implications in the regulation of antitumor immune response influencing immune cell differentiation and function. 1 , 78 , 79 In our study, the MPS2 subgroup had abundant infiltration of immune cells with antitumor function and higher expression of immune molecules, whereas immune dysregulation within the TME prevented the immune cells from exerting their full effects in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has suggested that immune cells play a major and complex role in tumor progression [ [29] , [30] , [31] ]. A previous investigation revealed the gene GGTLC1 as a potential immune pathway mediator of treatment resistance in breast cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%